USAHA MIKRO, KECIL DAN MENENGAH SEBAGAI DINAMISATOR DAN STABILISATOR PEREKONOMIAN INDONESIA - -, Sunarso (Universitas Slamet Riyadi, 2007)
ABSTRACT Indonesia just convalesce from economic crisis and in course ofÂ economic growth to pursue various national development left behind effect of economic crisis. For that, challenge enable ness of middle and small micro effort at period to come quicken its enableness by pushing again work infrastructure of economics like bank, financial institution and of a kind to give support to enableness of middle and small micro effort, so that can become resilience bases and growth of economics of Indonesia. Challenge enableness of middle and small micro effortÂ to improve competitiveness and productivity so be able improve its market compartment, and also diversify and its product differentiating in market Keywords: small industry, economic growth, product development